2020
DOI: 10.1111/jppi.12347
|View full text |Cite
|
Sign up to set email alerts
|

Trauma‐Specific Treatment for Individuals With Intellectual and Developmental Disabilities: A Review of the Literature From 2008 to 2018

Abstract: Background: Individuals with intellectual and developmental disabilities (IDD) are at increased risk for adverse experiences and developing posttraumatic stress disorder (PTSD). However, trauma and PTSD in this population are frequently underdiagnosed and undertreated. Despite the availability of multiple types of trauma-specific treatments for the general population, there is a gap in understanding these collective interventions within the IDD literature. Specific Aims: The aim of this article was to conduct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 53 publications
2
19
1
Order By: Relevance
“…Contrary to the findings of previous studies (Keesler, 2020; P. M. Sullivan & Knutson, 2000), we found no direct effect of ACE on ID. This indicates that forensic psychiatric patients who experienced more ACE have an equal chance of belonging to the ID group as those who experienced no or less ACE.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the findings of previous studies (Keesler, 2020; P. M. Sullivan & Knutson, 2000), we found no direct effect of ACE on ID. This indicates that forensic psychiatric patients who experienced more ACE have an equal chance of belonging to the ID group as those who experienced no or less ACE.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, individuals with ID are not only at higher risk of being violent toward others but are also often victims of violence themselves (Hassiotis et al, 2019;Keesler, 2020;Kunst et al, 2011). Exposure to adverse childhood experiences (ACE) can be attributed to a combination of characteristics of their disability and impaired family functioning due to that disability (Wigham & Emerson, 2015).…”
mentioning
confidence: 99%
“… Interventions & practices have often originated in the general population & have lacked sensitivity to disability identity and culture. As such, they frequently require adaptations to be effective (Andrews et al, 2019;Keesler, 2020).  The efficacy of disability services in facilitating community inclusion is unclear due an absence of evaluation & research.…”
Section: Lack Of Clarity In Defining Community Inclusionmentioning
confidence: 99%
“…Notably, both social work and the field of IDD have called for greater emphasis on best practices and EBP (Schalock et al, 2017;Thyer & Myers, 2011). For people with IDD, interventions and practices have often originated in the general population, and as such, they have lacked sensitivity to disability culture and therefore warrant adaptations to be effective (Andrews et al, 2019;Keesler, 2020). Schalock et al (2017) identified the importance of EBP in IDD services and emphasized a multi-systems framework with implications of various factors (e.g., support staff strategies and opportunities for participation) for individual outcomes.…”
Section: Lack Of Clarity In Defining Community Inclusionmentioning
confidence: 99%
“…The experiences and outcomes in this study may differ from those among therapists with different levels of expertise with trauma treatment, PC, or intellectual/developmental disabilities. Research examining trauma treatment among people with intellectual/developmental disabilities has often noted a lack of strategies to ensure treatment fidelity (Byrne, 2020; Keesler, 2020). To bolster the reliability and validity of the intervention, this study integrated a standardised training, had a single therapist (which can remove variability associated with multiple therapists), implemented a protocol checklist for the therapist to self‐monitor, included monthly team meetings, and ongoing consultation with the training expert.…”
Section: Strengths Limitations and Recommendationsmentioning
confidence: 99%